Cytotoxic activity of quinolinequinones in cancer: In vitro studies, molecular docking, and ADME/PK profiling - (:unkn) unknown (My University, 2023)
Lead molecules containing 1,4-quinone moiety are intriguing novel compounds that can be utilized to treat cancer owing to their antiproliferative activities. Nine previously reported quinolinequinones (AQQ1-9) were studied to better understand their inhibitory profile to produce potent and possibly safe lead molecules. The National Cancer Institute (NCI) of Bethesda chose all quinolinequinones (AQQ1-9) based on the NCI Developmental Therapeutics Program and tested them against a panel of 60 cancer cell lines. At a single dose and five further doses, AQQ7 significantly inhibited the proliferation of all leukemia cell lines and some breast cancer cell lines. We investigated the in vitro cytotoxic activities of the most promising compounds, AQQ2 and AQQ7, in MCF7 and T-47D breast cancer cells, DU-145 prostate cancer cells, HCT-116 and COLO 205 colon cancer cell lines, and HaCaT human keratinocytes using the MTT assay. AQQ7 showed particularly high cytotoxicity against MCF7 cells. Further analysis showed that AQQ7 exhibits anticancer activity through the induction of apoptosis without causing cell cycle arrest or oxidative stress. Molecular docking simulations for AQQ2 and AQQ7 were conducted against the COX, PTEN, and EGFR proteins, which are commonly overexpressed in breast, cervical, and prostate cancers. The in vitro ADME and in vivo PK profiling of these compounds have also been reported.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Health Sciences; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Mikrobiyoloji; KİMYA, ORGANİK; FARMAKOLOJİ VE ECZACILIK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; CHEMISTRY, ORGANIC; PHARMACOLOGY & PHARMACY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmakoloji; İlaç Keşfi; Organik Kimya; Fizik Bilimleri; Molecular Medicine; Pharmacology; Drug Discovery; Organic Chemistry; Physical Sciences; ADME; anticancer activity; breast cancer; cytotoxicity; leukemia; molecular docking